The Labyrinth. Enigma, Dialectics and the Origin of Philosophy in Giorgio Colli's Thought - Adán, Oscar (1997)
In this paper the A.intends to offer a view as complete as possible of the insights of the ltalian philosopher and critic Giorgio Colli on the origin of Greek philosophy. With aspecial emphasis on Nietzsche's Apollony an paradigm, Colli views the origin of the rational lagos as found in thes ages of the Archaic period and their interpretation of Apollos's oracle -whichappears to men as an enigma. From this origin will emerge two basic characteristics of archaic thought which will later appear in philosophy: its polemicand its destructive character.